Effectiveness of a video-based therapy program at home after acute stroke: a randomized controlled trial - Redzuan, N.S.; Julia, P.E.; Mazlan, M.; Abdullah, S.J.F. (2012)
Redzuan NS, Engkasan JP, Mazlan M, Freddy Abdullah Si. Effectiveness of a video-based therapy program at home after acute stroke: a randomized controlled trial. Arch Phys Med Rehabil 2012;93:2177-83. Objective: To evaluate the effectiveness of an intervention using video to deliver therapy at home for patients with stroke. Design: Randomized controlled trial. Setting: The neurology ward and rehabilitation medicine department of a tertiary hospital. Participants: Patients with stroke (N=90). There were 44 patients in the intervention group and 46 patients in the control group. Interventions: The intervention group received a combination of at-home rehabilitation guided by a digital videodisk containing therapy techniques and twice-monthly outpatient follow-up for 3 months. The conventional therapy group (control) attended weekly outpatient therapy sessions. Main Outcome Measures: The primary outcome measure was the modified Barthel Index (MBI) score. The secondary measures were the incidence of poststroke complications and the Caregiver Strain Index. Results: At 3 months, there were no significant differences with regard to the number of patients with improved MBI score, complication rate, or Caregiver Strain Index score between the 2 groups. Both groups had significant increases in the MBI score at 3 months (P<.001 for both groups). Regression analysis revealed that only stroke severity significantly influenced the MBI score (P<.001), complication rate (P<.01), and caregiver stress level (P<.05). Conclusions: Video-based therapy at home for post-acute stroke patients is safe, does not negatively impact independence, and is not stressful for caregivers.